St. John le calviniste, ou l’émule de Gil-Martin - Jean Berton (Revue LISA)
This article aims to show how far Hogg’s archetypal character, Gil-Martin, influenced Charlotte Brontë’s enigmatic character, St. John, who appears in chapters XXVI to XXXV and is mentioned again in the conclusion of Jane Eyre. Some unexpected words, like “glen”, in a greater Yorkshire area, operate as keywords to a “deep context” study in a neo-contextualist approach. Even though St. John cannot be mistaken for a double of Gil-Martin, a fair number of details tend to prove that James Hogg’s Private Memoirs and Confessions of a Justified Sinner deeply influenced Charlotte Brontë—both pride-driven St. John and Gil-Martin stand for demonic despotism. Yet, if Gil-Martin is a straightforward Gothic illustration of Satan, St. John is a reincarnation of a marble-cold Apollo in a dogma-trapped Calvinist. Brontë’s intention was not so much to denounce noxious excesses in religious beliefs as to set her heroine’s wise independence against nefarious male domination: whereas victimised Robert Wringhim is driven to despair and suicide, self-reliant Jane Eyre escapes from St. John’s grip. In both narratives relationships between men and women are shown as tragically warped by religious behavioural extravagance, but only the female character is granted a positive outcome to serve an optimistic view on life: Robert Wringhim is violently wrung out of the society of men and women, St. John Rivers, from “Marsh End”, blindly drifts away to his death in India, and airy Jane, of “Moor House”, wafts away to anchor to Edward Rochester, the sender of the airwave-born call.